2022
DOI: 10.1007/s11764-022-01196-x
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring work participation support for cancer survivors using the stages of change: perspectives of (health care) professionals and survivors

Abstract: Purpose Interventions to support work participation in cancer survivors (CSs) have shown limited effectiveness. Applying a behavioral change framework (e.g., stages of change) could make work participation interventions for CSs more timely and tailored. We aimed to explore the application of the stages of change framework to work participation support for CSs and to generate stage-specific intervention content. Methods Eighteen experts (e.g., occupational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
(79 reference statements)
1
8
0
Order By: Relevance
“…Both interns were supervised by authors ADZ, LB, and SFAD (a PhD candidate, postdoctoral researcher, and senior researcher, respectively, all with a research focus on psychosocial oncology and/or palliative care). ADZ, LB, and SFAD have experience in conducting qualitative research (e.g., Zegers et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both interns were supervised by authors ADZ, LB, and SFAD (a PhD candidate, postdoctoral researcher, and senior researcher, respectively, all with a research focus on psychosocial oncology and/or palliative care). ADZ, LB, and SFAD have experience in conducting qualitative research (e.g., Zegers et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the ability to work can offer cancer patients a sense of identity and purpose (Chow et al, 2015 ; Faas, 2018 ; Greidanus et al, 2018 ). However, many cancer patients experience barriers when resuming work during or after treatment, for example, fatigue (Nielsen et al, 2019 ; Paltrinieri et al, 2018 ; Zegers et al, 2022 ). For those with advanced cancer, additional barriers may arise due to disease progression, symptom burden, and/or ongoing (palliative) treatments (Glare et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 64 When developing such an intervention, lessons can be learned from other cancer survivorship interventions that are personalized, such as OncoKompas. 65 Another example of how an intervention can be tailored to the needs of specific cancer survivors is the STEPS intervention, 66 in which a behavioural change framework is used to adapt a work participation intervention to the ‘stage of change’ a particular cancer survivor is in.…”
Section: Growing Points and Areas Timely For Developing Researchmentioning
confidence: 99%
“…Duijts et al identified the Transtheoretical Model of Behavior Change (TTM) as a relevant theoretical framework for developing these interventions [14,15]. A recent qualitative study endorses the value of tailoring support for the work participation of cancer survivors along the stages of change described by the TTM [16]. However, the TTM alone cannot account for all the complexities of behavior change, particularly when studying the multidimensional process of RTW [13,14].…”
Section: Introductionmentioning
confidence: 99%